Ferramentas didáticas no ensino de óptica : uma pesquisa aplicada com educandos do terceiro ano do ensino médio de Rio Branco-MT - Moreira, Alzira Silva (2020)
This work presents the results of a research applied in students of the high school third grade in a state school in Rio Branco-MT. Thus, for the execution of this work, a didactic resource with 20 different activities was used, one being the didactic game and the objective was to answer whether these resources contribute or not to the teaching and learning process, taking the theoretical approach as Meaningful Learning in Physics, focused on Experimental Work in the field of Geometric Optics and Physical Optics. For this purpose, the qualitative approach was used, in order to detail the collections of information through questionnaires of entry and exit and observation during classes, as a parameter of comparison and analysis to obtain results. In addition to the nineteen teaching resources, there was the application of the last resource, which was a pedagogical game, as a tool to recap the concepts worked on, since the content worked in the classroom, during this research, refers to the content of the year. previous (high school high school degree). Among the research objectives, the highlight is to promote interaction and integration between students, motivation and the spirit of competition. It was observed that the students' motivation to participate in the activities made the proposal more significant for the realization of classes outside the traditional daily life. The practical activities provided subsidies to the teacher and students, which aroused the interest in seeking, interacting, reflecting, arguing, reasoning, expressing their ideas, developing the motivation to learn and the interest in the theme studied.